Paula Galenieka disertācija “Latvijas rozes” - Jamonte, Daiga (My University, 2021)
Atzīmējot botāniķa Paula Galenieka (1891-1962) 130 gadu jubileju par LU Muzeja 2021. gada februāra mēneša priekšmetu tika izvēlēts muzeja jaunieguvums profesora disertācija “Latvijas rozes”, kas tika aizstāvēta 1936. gadā. Rakstā sniegts ieskats par disertāciju un tās tapšanu.

Celebrating the 130th anniversary of the botanist Pauls Galenieks (1891-1962), the new acquisition of the museum, the professor's dissertation “Latvian Roses”, which was defended in 1936, was chosen as the subject of the Museum of the University of Latvia in February 2021. The article provides an insight into the dissertation and its creation.
Paul Galenieks' dissertation “Latvian roses”
Keywords: Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects; Pauls Galenieks; savvaļas rozes; botany; Rosa